CJCA Toolkit: Recruiting, hiring and retaining qualified staff. - Pette, Sharon; Dempsey, Michael (Corrections Today)
The article discusses the "CJCA Toolkit: Recruiting, Hiring, and Retaining Qualified Staff" released by the Council of Juvenile Correctional Administrators (CJCA) in the U.S. in January 2019. It describes the use of the toolkit by juvenile justice facilities and other social service sectors to explore or improve strategies for recruiting, hiring and retaining direct care staff. It also explains factors and strategies for retaining qualified direct care staff.